Synthesis of polyaniline nanoparticles for fluorescence sensing applications - Lan, Tian (2016)
Conventional fluorophores are unable to meet the demands of modern applications which requires higher-sensitivity and high-throughput. With advancement in nanotechnology, extraordinary brightness, fast and stable emission rates, excellent photostability, and non-toxic features exhibited by polymer nanoparticles attracted considerable attention. These features indicate the great potential of polymer nanoparticles for fluorescence sensing in chemical and biological applications. In this report, polyaniline nanoparticles (PANI NPs) were synthesized from aniline monomer with electropolymerization techniques in ionic liquid and sonication method. The electropolymerization process have been optimized and PANI NPs are characterized for its optical properties. PANI NPs were successfully synthesized after sonicating the PANI film in NMP. The amorphous nature, average size, thickness and networking structure of PANI film were characterized by AFM, SEM and TEM results. Conducting emeraldine salt formation was confirmed through the FTIR results. The conductivity of PANI NPs indicate their optical properties as fluorescence sensor. Further concentration-dependent studies for enhancement effect of PANI NPs on lead ion and pH dependent studies are still ongoing.